Interactionism vs epiphenomenalism : unclosing the causal closure of the physical - Сепетий, Дмитро Петрович (My University, 2017)
The paper considers the issue of the causal closure of the physical in the perspective of the mind-body dualism. The two alternative dualist views, interactionism and epiphenomenalism, are compared. The main arguments for the causal closure of the physical (against interactionism), as formulated by David Chalmers, are critically discussed and found lacking. With respect to epiphenomenalism, it is argued that it suffers from several major deficiencies that make it untenable: it is practically unacceptable, because all our conscious practical activities are necessarily based on the assumption that our desires, plans, and ideas can influence our behaviour, which consists of physical events; it implies that all biological evolution and human history would be exactly as they are even if there was no consciousness; it leaves its adherent without reasons to believe that other human beings have consciousness and that his or her ideas about the physical world have anything to do with
Keywords: mental; physical; materialism; dualism; interactionism; epiphenomenalism